Computational fluid dynamics a practical approach - Tu, Jiyuan (Butterworth-Heinemann, 2008)
A senior level undergraduate and graduate textbook for a wide audience of engineering students taking a first course in CFD or Computer Aided Engineering. Fully course matched, with the most extensive and rigorous pedagogy and features of any book in the field. The first book in the field aimed at CFD users rather than developers. The only course text available that is specifically designed to give an applications lead, software oriented approach to understanding and using CFD. This is coupled with a complete grounding in the necessary mathematical principles of CFD. Unlike existing books this has not been written with the needs of advanced students who are expected to develop their own CFD code in mind. The widespread availability of commercial software enables this book to meet the needs of beginner CFD students who use commercial software. Meets the needs of students taking a wide range of courses. Unlike existing titles it does not focus on the needs of advanced aerospace or applied math courses. Ideal for use on the burgeoning courses in mechanical, automotive, marine, environmental, civil and chemical engineering that harness CFD or computer aided engineering more generally. The strongest pedagogy of any available book. Core mathematics are developed in a step by step fashion, with no assumed steps left out in order to develop a solid understanding of the conservation laws, mathematical transport equations and basic concepts of fluid mechanics and heat transfer that comprise the key to effective use of CFD Detailed worked examples reinforce learning and link to the real applications students will work with; end of chapter knowledge check exercises, homework assignment questions, plus separate Instructor's Manual.
Keywords: Fluid dynamics.; Heat -- Transmission.; Turbulence.; elektronické knihy; electronic books